GA KANEMO WOLO III (Gã Reading Book III) - (:unkn) unknown (Evangelical Missionary Society, 1895)
This 1895 second edition of "GA KANEMO WOLO III" is a Gã-language reading book published by the Evangelical Missionary Society for use in vernacular schools on the Gold Coast (modern Ghana). It functions as a comprehensive educational tool, combining literacy instruction with religious and cultural content. The book includes the biography of the missionary Henry Wharton, a vast collection of Gã proverbs, translated Biblical passages, practical document samples, and detailed geographical and historical accounts of the Ga people and their region. Its primary purpose was to promote literacy and Christian evangelism while also documenting and preserving local language and culture within a missionary framework
This 1895 second edition of "GA KANEMO WOLO III" is a Gã-language reading book published by the Evangelical Missionary Society for use in vernacular schools on the Gold Coast (modern Ghana). It functions as a comprehensive educational tool, combining literacy instruction with religious and cultural content. The book includes the biography of the missionary Henry Wharton, a vast collection of Gã proverbs, translated Biblical passages, practical document samples, and detailed geographical and historical accounts of the Ga people and their region. Its primary purpose was to promote literacy and Christian evangelism while also documenting and preserving local language and culture within a missionary framework
Keywords: Vernacular Education; Gã Language; Gã Proverbs; Ga-Adangme; Basel Mission; Gold Coast